The controlling nutritional status score and risk factors associated with malnutrition in patients with acute ischemic stroke - Chen, Yuanyuan; Yang, Hongyan; Lan, Meijuan; Wei, Hui; Chen, Yanqin (Frontiers in Neurology, 2023)
Objectives Malnutrition is an independent risk factor for poor outcomes in patients who suffered an acute ischemic stroke (AIS). The controlling nutritional status (CONUT) score can provide information for nutritional management in AIS patients. However, the risk factors associated with the CONUT score have not been established to date. Therefore, in this study, we aimed to investigate the CONUT score of patients with AIS and explore the potential risk factors associated with it. Methods We conducted a retrospective review of the data from consecutive AIS patients who were recruited in the CIRCLE study. Within 2 days of admission, we gathered the CONUT score, the Nutritional Risk Screening 2002, the Modified Rankin Scale, the National Institutes of Health Neurological Deficit Score (NIHSS), and demographic data from medical records. We used chi-squared tests to examine admission, and a logistic regression analysis was performed to explore the risk factors associated with CONUT in patients with AIS. Results A total of 231 patients with AIS participated in the study, with a mean age of 62.32 ± 13.0 years and a mean NIHSS of 6.77 ± 3.8. Of these patients, 41(17.7%) had hyperlipidemia. In terms of nutritional assessment, 137(59.3%) patients with AIS had high CONUT scores, 86(37.2%) patients with AIS had low or high BMI, and 117(50.6%) patients with AIS had NRS-2002 scores below 3. The chi-squared tests showed that age, NIHSS, body mass index (BMI), and hyperlipidemia were associated with the CONUT score (P < 0.05). The logistic regression analysis showed that low NIHSS scores (OR = 0.055 95% CI: 0.003–0.893), younger age (OR = 0.159 95% CI: 0.054–0.469), and hyperlipidemia (OR = 0.303 95% CI: 0.141–0.648) were independently associated with lower CONUT scores (P < 0.05), whereas BMI was not found to be independently associated with the CONUT. Conclusions More than half of the patients with AIS were at risk of malnutrition, with age and neurological deficits being identified as risk factors for nutritional control. Hyperlipidemia was found to be a protective factor of the CONUT, while NRS-2002 and BMI did not affect the nutritional control in patients with AIS.